Combined calcium looping and chemical looping combustion cycles with CaO–CuO pellets in a fixed bed reactor. (1st August 2015) - Ridha, Firas N.; Lu, Dennis; Macchi, Arturo; Hughes, Robin W.
Highlights: Combined CaL–CLC system in a fixed bed reactor is a feasible process. Mixed pellets exhibited the highest CO2 uptakes of 0.11 g CO2 /g bed in the first cycle. The reduction of CuO to Cu2 O is partially irreversible. Among all pellets, mixed pellets are the most promising for CaL–CLC combined cycles. Abstract: The feasibility of using integrated CaO/CuO-based pellets in combined calcium and chemical looping cycles in a fixed bed was investigated with emphasis on CO2 capture performance. Three types of pellets were tested, namely; integrated core-in-shell CaO/CuO-based pellets; integrated homogeneous CaO/CuO-based pellets; and mixed CaO-based pellets and CuO-based pellets. Redox cycles consisted of oxidation/carbonation at 650 °C in 15% CO2 ; 4% O2, and N2 balance, and reduction/calcination at 850 °C in a CO/H2 mixture. The results showed that mixed pellets exhibited the highest CO2 uptakes of 0.11 g CO2 /g bed in the first cycle and 0.07 g/g after 11 cycles (corresponding to CaO conversions of 32.1% and 19%, respectively). This enhanced performance was attributed to the significantly higher pore volume and surface area in the calcined CaO-based pellets, which were superior to those of integrated CaO/CuO-based pellets. The reduction of CuO to Cu2 O was found to be partially irreversible, with ∼45% of copper oxide in the pellets in the form of Cu2 O despite the excess O2 in the oxidizing environment. It was also noted that cycled core-in-shell pellets were the most susceptible to fragmentation, indicating the low mechanical strength of these pellets. It was concluded that combined calcium and chemical looping cycles in a fixed bed system is a feasible process providing suitable pellets are used. Incorporating CuO in CaO-based pellets reduces the porosity of the pellets, thus compromises CO2 uptake. Among the three groups of pellets, mixed pellets are the most promising for CaL–CLC processes due to their better performance, easier manufacturing, and better quality control than integrated pellets.